Evaluation of the Hippocampal Normal Tissue Complication Model in a Prospective Cohort of Low Grade Glioma Patients—An Analysis Within the EORTC 22033 Clinical Trial - Jaspers, Jaap; Mèndez Romero, Alejandra; Hoogeman, Mischa S.; van den Bent, Martin; Wiggenraad, Ruud G. J.; Taphoorn, Martin J. B.; Eekers, Danielle B. P.; Lagerwaard, Frank J.; Lucas Calduch, Anna Maria; Baumert, Brigitta G.; Klein, Martin (Frontiers in Oncology, 2019)
Purpose: To evaluate the performance of the hippocampal normal tissue complication model that relates dose to the bilateral hippocampus to memory impairment at 18 months post-treatment in a population of low-grade glioma (LGG) patients. Methods: LGG patients treated within the radiotherapy-only arm of the EORTC 22033-26033 trial were analyzed. Hippocampal dose parameters were calculated from the original radiotherapy plans. Difference in Rey Verbal Auditory Learning test delayed recall (AVLT-DR) performance pre-and 18 (±4) months post-treatment was compared to reference data from the Maastricht Aging study. The NTCP model published by Gondi et al. was applied to the dosimetric data and model predictions were compared to actual neurocognitive outcome. Results: A total of 29 patients met inclusion criteria. Mean dose in EQD2 Gy to the bilateral hippocampus was 39.8 Gy (95% CI 34.3–44.4 Gy), the median dose to 40% of the bilateral hippocampus was 47.2 EQD2 Gy. The model predicted a risk of memory impairment exceeding 99% in 22 patients. However, only seven patients were found to have a significant decline in AVLT-dr score. Conclusions: In this dataset of only LGG patients treated with radiotherapy the hippocampus NTCP model did not perform as expected to predict cognitive decline based on dose to 40% of the bilateral hippocampus. Caution should be taken when extrapolating this model outside of the range of dose-volume parameters in which it was developed.